Juridical Review of E-commerce Selling and Buying on Consumers and Buyers in Indonesia - Aris Surya Muzakki; Suraji Suraji (Asosiasi Riset Ilmu Pendidikan Indonesia, 2024)
The use of e-commerce in the world of trade has had a huge impact on Indonesian society, this is related to very important legal issues. The importance of legal issues in the field of E-commerce, especially in providing legal protection for consumers who carry out buying and selling transactions via the Internet. This development emerged due to offers and acceptance from the public, as evidenced by the emergence of various online stores such as Kaskus, Tokopedia, Bukalapak, Shopee and Lazada. This research aims to find out and analyze legal protection for consumers in online buying and selling transactions (e-commerce) and to find out and analyze legal remedies that can be taken by consumers if there is a default in online buying and selling transactions (e-commerce). The approach method used in this research is a normative juridical approach. The specification of this research is descriptive analysis. The data source used is secondary data, which consists of primary, secondary and tertiary law. The data collection tool is library research. The data analysis technique used is qualitative analysis. The results of this research and discussion are legal protection for e-commerce users by upholding consumer rights in accordance with Law Number 8 of 1999 concerning Consumer Protection articles 19, 20, 21, 24, and 26 and regulations related to the implementation of online buying and selling (e-commerce) and the implementation of consumer protection is also supported by involving several parties such as the government, national consumer protection bodies and non-governmental consumer protection institutions. Legal efforts that can be taken to resolve defaults in Law Number 8 of 1999 concerning Consumer Protection are litigation and non-litigation.